2016
DOI: 10.1371/journal.pone.0151286
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Protease in the Fission Yeast Schizosaccharomyces pombe

Abstract: BackgroundHIV-1 protease (PR) is an essential viral enzyme. Its primary function is to proteolyze the viral Gag-Pol polyprotein for production of viral enzymes and structural proteins and for maturation of infectious viral particles. Increasing evidence suggests that PR cleaves host cellular proteins. However, the nature of PR-host cellular protein interactions is elusive. This study aimed to develop a fission yeast (Schizosaccharomyces pombe) model system and to examine the possible interaction of HIV-1 PR wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(78 citation statements)
references
References 56 publications
3
75
0
Order By: Relevance
“…Our prior results have shown that the wt PR cleaved the indigenous HIV-1 MA↓CA (DSQNY↓PIVQ) and p6 (DSFNF↓PQIT) viral targets in the fission yeast as it does in the HIV-1 infection of mammalian cells, suggesting that the protease activity of HIV-1 wt PR in fission yeast was similar to that in mammalian cells [32]. The experiment conducted here was aimed to test whether the three clinically isolated HIV-1 mdr PRs were also functional as PR enzymes in fission yeast.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our prior results have shown that the wt PR cleaved the indigenous HIV-1 MA↓CA (DSQNY↓PIVQ) and p6 (DSFNF↓PQIT) viral targets in the fission yeast as it does in the HIV-1 infection of mammalian cells, suggesting that the protease activity of HIV-1 wt PR in fission yeast was similar to that in mammalian cells [32]. The experiment conducted here was aimed to test whether the three clinically isolated HIV-1 mdr PRs were also functional as PR enzymes in fission yeast.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, separation of GFP from Vpr due to the PR cleavage at either the MA↓CA (DSQNY↓PIVQ) or the p6 (DSFNF↓PQIT) substrate site will lead to the “GFP pattern,” i.e., with uniform distribution throughout cells [35]. Note that our early test results showed that the PR-mediated cleavages on the MA↓CA (DSQNY↓PIVQ) and on the p6 (DSFNF↓PQIT) substrates were target specific, and the wt PR by itself did not interfere with the intracellular localization of GFP or GFP-tagged Vpr in the fission yeast [32]. Therefore, we were able to measure the specific enzymatic activities of HIV-1 mdr PR as designed.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell viability was evaluated by Trypan blue staining (50) and by a commercial live/dead yeast viability assay (Invitrogen) (47,51). Trypan blue is a diazo dye that stains only dead cells; live cells with intact cell membranes are not stained.…”
Section: Methodsmentioning
confidence: 99%